The comparison of the relationship between body composition and physical fitness in students of sports championship classes in early specialized (gymnastics) and late specialized (judo) sports - Kuczyński, Gracjan; Prokopczyk, Adam (Journal of Education, Health and Sport, 2025)
Backgrounds The purpose of this study is to compare the level of physical fitness and the effect of body composition on the level of physical fitness in boys training in sports at the elementary school level in early specialization sports (gymnastic sports), non-early specialization sports (judo) and in classes not training in competitive sports. Material and methods. The study included students in the gymnastics-sports-jumping trampoline classes (n=8), with an average age of 11.54; judo classes (n=11) with an average age of 12.66; and general classes (n=25) with an average age of 12.21 at the elementary school level. Results. Among the subjects, the highest level of physical fitness was shown in students participating in gymnastic sports, followed by those training judo and students not participating in competitive sports. There was a significant difference in fitness levels between students of early specialty sports and non-sports students, as well as the effect of body composition on fitness levels in all the groups studied. Conclusion. In order to optimize the training process, it is necessary to introduce individualized diets adapted to the training process in the sports championship classes, as well as classes on proper nutrition in sports and everyday life taking into account the puberty process.